2014
DOI: 10.1155/2014/565284
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E rORF2p Stimulated and Unstimulated Peripheral Expression Profiling in Patients with Self-Limiting Hepatitis E Infection

Abstract: To improve the current knowledge on the involvement of peripheral lymphocytes in hepatitis E virus (HEV) associated pathogenesis, we analyzed alterations in (1) immunophenotypic expressions (by flow cytometry) and (2) gene expression patterns (by TaqMan Low Density Array) of activatory, inhibitory, integrin, homing, ectonucleotidase machinery, costimulatory, inflammatory markers, and T regulatory cells (Treg) associated cytokines on HEV rORF2p stimulated and unstimulated PBMCs of 43 acute HEV patients, 30 reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Based on the reduced percentages of NK cells in COVID-19 patients and the well-known antiviral role of NK cells, it has been speculated that the restoration of NK cells and their function may be a near-future solution for COVID-19 patients 1 15 18 23 . In our study asymptomatic, mild symptomatic patients and recovered individuals demonstrated a similar low NK cell profile, consistent with other reports.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the reduced percentages of NK cells in COVID-19 patients and the well-known antiviral role of NK cells, it has been speculated that the restoration of NK cells and their function may be a near-future solution for COVID-19 patients 1 15 18 23 . In our study asymptomatic, mild symptomatic patients and recovered individuals demonstrated a similar low NK cell profile, consistent with other reports.…”
Section: Discussionmentioning
confidence: 99%
“…Natural Killer (NK) and NKT cells, T-cells and subsets, B and B memory cells, T regulatory cells (Tregs) enumeration : Freshly isolated peripheral blood mononuclear cells (PBMCs) (0.5 X 10 5 ) from all study participants were stained with antibodies specific for NK and NKT, T and subsets, B and B memory, T regulatory (Tregs) cells using anti-human CD3PerCP (cloneSK7), CD56APC (cloneNCAM16.2), CD4PE (cloneRPAT4), CD8APCH7 (cloneRPAT8), CD19PECy7 (cloneSJ25C1), CD27APCH7 (cloneM-T271), CD45ROAPC (cloneUCHL1) monoclonal antibodies and Treg cocktail [CD127Alexa Fluor 647 (clone HIL-7R), CD25PE-Cy7, CD4FITC (clone7RM21|2A3|SK3)] as previously described 12 13 14 15 16 . PE-Cy™7 Mouse IgG1 κ Isotype Control (BD Biosciences, San Jose, CA, USA) was used as negative control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, comprehensive in vitro and in vivo studies have explored the mechanisms of inflammation and host immune response in acute hepatitis E patients [ 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 ]. For instance, immunohistochemistry staining of liver biopsy samples of patients diagnosed with HEV-related acute liver failure showed an increased infiltration of cytotoxic T-cells (CD3, CD8), natural killer cells (NK-cells; CD56) and helper T-cells (CD4) compared to liver biopsies of healthy patients [ 95 ].…”
Section: Putative Molecular Factors Involved In Hev-mediated Hcc—hallmarks Of Cancermentioning
confidence: 99%
“…Hepatitis E virus (HEV) is a non-enveloped, positive sense single-stranded RNA virus that belongs to the family Hepeviridae ( Smith et al, 2014 ), which is one of the main causes of acute hepatitis in humans and many other species ( Martin-Latil et al, 2016 ; Donnelly et al, 2017 ). Although, hepatitis E is largely a self-limiting disease ( Rathod and Tripathy, 2014 , 2016 ), pregnant women and fetals are exceptionally susceptible to HEV infection ( Nan et al, 2017 ; Verma et al, 2017 ). The mortality rate of pregnant women in the third trimester of pregnancy infected with HEV is as high as 25%, extremely easy to death of the mother and fetus, abortion, premature delivery or stillbirth ( Mancinelli et al, 2017 ; Naru et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%